Key informant perspectives on sexual health services for travelling young adults: a qualitative study - Emmanuelle Gareau; Karen P. Phillips (BMC, 2022)
Abstract Background International travel has become increasingly popular among young adults. Young adults often engage in casual sexual relationships abroad, exhibit sexual risk behaviours and may thus be at risk of contracting sexually transmitted and blood-borne infections. Pre-travel interventions and consultations may mitigate this risk. At present, we know little about sexual health-related pre-travel interventions. The aim of this study was therefore to document key informants' experiences, perceptions and recommendations in the context of sexual health of young adult travellers. Methods Key informants were professionals working in Ottawa, Canada travel clinics, travel organizations or sexual health clinics with a young adult clientele. This study used a qualitative approach and consisted of 13 in-person or Skype semi-structured interviews with key informants. Thematic content analysis was informed by a sexual health framework, with themes emerging both inductively and deductively. Results Sexual health was not common in pre-travel interventions described by key informants. Risk-assessment, and practical or purpose-driven pre-travel interventions were identified, resulting in risk mitigation strategies tailored to the destination region and/or mission/culture of the travel organization. Dissemination (e.g. limited time, lack of training) and uptake (e.g. young adults' embarrassment, provider discomfort, financial constraints) barriers limited in-depth discussions of pre-travel interventions related to sexual health. Key informants acknowledged the importance of early sexual health education, and recommended ongoing, comprehensive sexual education for both youth and young adults. Conclusion The findings of this study suggest that more time and resources should be allocated to the topic of sexual health during pre-travel interventions with young adults. Professionals who guide and prepare young adults for travel must develop concomitant skills in sexual health promotion. Early, comprehensive sexual education is recommended to improve overall sexual health in young adults and mitigate risk behaviours during travel.